Synthesis of LiMn2O4 with Outstanding Lithium‐Insertion Kinetics and Long‐Term Stability. Issue 9 (25th July 2014) - Laszczynski, Nina; von Zamory, Jan; Loeffler, Nicholas; Cho, Gyu Bong; Kim, Guk‐Tae; Passerini, Stefano
Abstract A simple route for the synthesis of LiMn2O4 (LMO) at low calcination temperatures is proposed. The calcination temperature is known to influence the structure and surface morphology of LMO; therefore, materials synthesized at different temperatures are characterized by using different techniques. A correlation between the calcination temperature and the structure and surface morphology of the material is shown. The synthesis route described here works at low calcination temperatures (650 °C), which leads to LMO that has an excellent rate performance (110 mAh g−1) at a charge/discharge rate of 100 C, and avoids cation mixing, manganese dissolution, and Jahn–Teller distortion. The obtained morphology of octahedrons showing primarily (111) planes, ensures excellent electrochemical performance and stability.